2019
DOI: 10.1029/2018jc014721
|View full text |Cite
|
Sign up to set email alerts
|

Bottom and Intermediate Nepheloid Layer Induced by Shoaling Internal Solitary Waves: Impacts of the Angle of the Wave Group Velocity Vector and Slope Gradients

Abstract: The widely recognized global phenomena of bottom nepheloid layer (BNL) and intermediate nepheloid layer (INL) are ubiquitous in the ocean. These phenomena are induced by shoaling internal solitary waves (ISWs), as observed in many studies. In this study, we analyzed the BNLs and INLs induced by shoaling ISWs and their detailed processes using flume experiments and field observations. ISWs suspended seabed sediment by the horizontal velocity in the vortex, and the near‐bottom vertical velocity lifted sediment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
(175 reference statements)
0
11
0
Order By: Relevance
“…Hosegood et al (2004), Cheriton et al (2014), Masunaga et al (2015), Bourgault et al (2014), and others have observed bottom and intermediate depth sediment layers (nepheloid layers) that formed due to NLIW interacting with a sloped shelf. This process has been demonstrated in laboratory studies (e.g., Tian et al, 2019) and qualitatively replicated in a 2D transect field-scale numerical model (Masunaga et al, 2017). The mechanisms for NLIW-induced sediment resuspension on flat bottoms and mild slopes remains speculative, with a recent review by Boegman and Stastna (2019) identifying the need for more process-oriented research in these areas.…”
Section: Introductionmentioning
confidence: 77%
“…Hosegood et al (2004), Cheriton et al (2014), Masunaga et al (2015), Bourgault et al (2014), and others have observed bottom and intermediate depth sediment layers (nepheloid layers) that formed due to NLIW interacting with a sloped shelf. This process has been demonstrated in laboratory studies (e.g., Tian et al, 2019) and qualitatively replicated in a 2D transect field-scale numerical model (Masunaga et al, 2017). The mechanisms for NLIW-induced sediment resuspension on flat bottoms and mild slopes remains speculative, with a recent review by Boegman and Stastna (2019) identifying the need for more process-oriented research in these areas.…”
Section: Introductionmentioning
confidence: 77%
“…As reported, vertical‐averaged geostrophic current speed from 2,400 m to the bottom in the northern SCS basin is slower than 1 cm/s (G. Wang et al., 2011). Sediment resuspension by internal waves in the northeastern SCS is observed at a maximum water depth of ∼1,500 m (Jia et al., 2019; Tian et al., 2019, 2021). Thus, direct riverine input or locus of active resuspension is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…seabed sediments, and controlling the grain size of the regional sediments (Ma et al, 2016;Tian et al, 2019aTian et al, ,b, 2021. The phenomena of sediment resuspension can be easily observed from high-resolution acoustic backscatter data (Cacchione et al, 2002;Reeder et al, 2011;Masunaga et al, 2015;Tian et al, 2019a).…”
Section: Internal Solitary Wave-induced Sediment Resuspensionmentioning
confidence: 99%
“…seabed sediments, and controlling the grain size of the regional sediments (Ma et al, 2016;Tian et al, 2019aTian et al, ,b, 2021. The phenomena of sediment resuspension can be easily observed from high-resolution acoustic backscatter data (Cacchione et al, 2002;Reeder et al, 2011;Masunaga et al, 2015;Tian et al, 2019a). In this study, patches of weak scattering intensity (purple arrows) are often observed in the near-bottom layers after passing the ISWs (Figures 7A,G), showing the sediment resuspension process induced by the ISWs.…”
Section: Internal Solitary Wave-induced Sediment Resuspensionmentioning
confidence: 99%
See 1 more Smart Citation